Soil Degradation as a Matter of Concern for Plato: A Few Notes in the Margin of Critias (110–112, Ed. Burnet) - Ilski, Kazimierz; Kotłowska, Anna (Studia Historiae Oeconomicae, 2024)
The aim of this article is to present the hypothesis that a powerful earthquake, which resulted in, among others, the destruction and engulfment by water of the bay of two cities, Helike and Bura (373/72 BC) may have been one of two significant causes for which Plato drew attention to soil degradation and erosion processes in Attica and their potentially devastating effects. The second reason was the personally experienced anthropogenic transformation of the natural environment. The philological and historical commentary on the dialogue Critias also showed that Plato, in his analysis, used contemporary terminology in the field of natural sciences.